A method of treating a copper alloy

CN122879642APending Publication Date: 2026-10-09CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611373678.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

该专利申请在避免铜合金因高温退火而软化的问题上取得了很大的进步,可在铜合金表面形成结合牢固的渗硅层,但是受喷丸处理所形成的变形层厚度以及固固扩散的制约,其所能形成的渗硅层的厚度也十分有限,使得其耐磨性能的提升还有相当大的空间

Benefits of technology

(1)本发明的处理方法可有效提高铜合金的耐磨性能,提升铜合金的服役寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a treatment method of copper alloy, comprising the following steps: embedding the copper alloy to be treated in a first siliconizing agent, placing in an atmosphere furnace with continuously-inhaled first mixed gas containing silane and hydrogen, heating to 450-610 DEG C, keeping warm for 2-3 hours, cooling, obtaining siliconized copper alloy; placing the siliconized copper alloy in constant-temperature hot water, keeping warm, obtaining constant-temperature copper alloy; performing rotary swaging treatment on the constant-temperature copper alloy, obtaining rotary swaged copper alloy; embedding the rotary swaged copper alloy in a second siliconizing agent, placing in an atmosphere furnace with continuously-inhaled second mixed gas containing silane and hydrogen, heating to 380-400 DEG C, keeping warm for 3-4 hours, and then cooling and discharging, and the treatment method is completed. The treatment method is helpful to form a secondary siliconized layer with greater thickness, more stable structure and closer combination with the copper alloy base material on the surface of the copper alloy, thereby significantly improving the wear resistance and service life of the copper alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for processing copper alloys, belonging to the field of alloy material manufacturing technology. Background Technology

[0002] Copper alloys are a widely used basic non-ferrous metal material in the engineering field. With their excellent properties such as high electrical and thermal conductivity, good fatigue and friction wear resistance, easy forming and machining, and good corrosion resistance under certain conditions, they have been widely used in many fields such as electrical instrumentation, chemical industry, shipbuilding, and aviation.

[0003] Copper alloys are widely used in bearings, typically acting as friction pairs with steel shafts during service. However, compared to steel shafts, copper alloys suffer from drawbacks such as lower strength, lower hardness, poorer oxidation resistance, and lower wear resistance, limiting their application. Generally, higher hardness of friction components results in better wear resistance; therefore, increasing the hardness of the working surface of copper alloys is an effective way to improve the wear resistance and service life of copper bearings.

[0004] To address the aforementioned shortcomings and defects, one common existing improvement method is to use plating treatments, such as electroplating, chemical plating, or silicon diffusion, to improve the surface properties of copper alloys. While these methods offer improvements, their effectiveness is not ideal and they suffer from problems such as high energy consumption and significant pollution. Silicon diffusion onto the surface of copper alloys is a better method for surface modification. Silicon itself is hard and is also a strengthening element for copper. By performing silicon diffusion treatment on the surface of copper alloys, a harder silicon-diffused layer can be formed, increasing the surface hardness of the copper alloy. This, in turn, improves the wear resistance of the friction surfaces of copper alloy components such as copper bearings, reduces the surface friction coefficient of copper alloy components, and extends their service life, demonstrating significant engineering application value.

[0005] There are various methods for siliconizing copper alloy surfaces, such as solid-state and gas-state methods. Although surface siliconizing can significantly improve the service life of copper alloys, current siliconizing processes, whether solid-state, liquid-state, or gas-state, typically involve high siliconizing temperatures, generally between 600 and 900°C. At temperatures above 600°C, copper alloy components such as bearings have already undergone complete annealing and softening. This complete annealing and softening is detrimental to the service life of copper alloy components like bearings, meaning that current siliconizing processes still have significant room for improvement.

[0006] Chinese invention patent application CN115896684A discloses a method for silicon diffusion on the surface of copper alloys, comprising the following steps: shot peening the copper alloy to be treated; placing the shot-peened copper alloy in a loading boat and filling the loading boat with a silicon diffusion agent so that the copper alloy is completely covered by the silicon diffusion agent; then placing the loading boat in an atmosphere furnace, continuously introducing a mixture of silane and hydrogen gas into the atmosphere furnace, heating to 380-420℃, holding at that temperature for 5-8 hours, and then cooling and removing from the furnace. This patent application has made significant progress in avoiding the softening of copper alloys due to high-temperature annealing, and can form a firmly bonded silicon diffusion layer on the surface of the copper alloy. However, due to the limitations of the thickness of the deformed layer formed by shot peening and solid-solid diffusion, the thickness of the silicon diffusion layer that can be formed is also very limited, leaving considerable room for improvement in its wear resistance. In addition, this patent application is only suitable for processing plates and strips. Summary of the Invention

[0007] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for processing copper alloys to obtain copper alloys with better wear resistance.

[0008] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows: A method for processing copper alloys includes the following steps: S1. Primary silicon diffusion: The copper alloy to be treated is buried in the first silicon diffusion agent and placed in an atmosphere furnace with a first mixed gas containing silane and hydrogen continuously introduced. The temperature is raised to 450-610℃, held for 2-3 hours, and then cooled to obtain silicon-dipped copper alloy. S2. Constant temperature treatment: The silicon-impregnated copper alloy is placed in hot water at a constant temperature to keep the temperature of the silicon-impregnated copper alloy constant at 70-90℃ to obtain a constant temperature copper alloy. S3. Rotary forging: The constant temperature copper alloy is subjected to rotary forging to obtain a rotary forged copper alloy. S4. Secondary silicon diffusion: The forged copper alloy is embedded in a second silicon diffusion agent and placed in an atmosphere furnace with a second mixed gas containing silane and hydrogen continuously introduced. The temperature is raised to 380-400℃, held for 3-4 hours, and then cooled and removed from the furnace.

[0009] Further, in S1, the copper alloy contains 61-65 wt% Cu, 3.0-5.0 wt% Al, 1.5-3.5 wt% Mn, and 0.4-1.2 wt% Si, with the balance being zinc and unavoidable impurities.

[0010] Furthermore, the content of impurity elements in the copper alloy is not higher than 1.5 wt%.

[0011] Optionally, the impurity element includes one or more of Sn and Ni; The content of Sn is no more than 0.3 wt%, and the content of Ni is no more than 0.3 wt%.

[0012] Optionally, the copper alloy is a copper alloy rod, preferably a cylindrical copper alloy rod.

[0013] Furthermore, in S1, the first siliconizing agent includes a silicon source, a silicon infiltration catalyst, an anti-sintering agent, and a filler, and the mass ratio of the silicon source, silicon infiltration catalyst, anti-sintering agent, and filler is 40-70:1-3:20-40:0-15; The silicon source is one or more of silicon powder and ferrosilicon powder; In the first gas mixture, the volume ratio of silane to hydrogen is 2:2.5-3.5.

[0014] Further, in S1, the temperature is raised to 480-580℃ and held for 2.2-2.8 hours. Optionally, the heating rate is 1-3℃ / min.

[0015] Further, in S2, the silicon-impregnated copper alloy is placed in a constant-temperature hot water at 70-90°C and treated at that temperature for 50-70 minutes.

[0016] Optionally, rotary forging can be performed immediately after S2; alternatively, between S2 and S3, the constant-temperature copper alloy can be kept warm with a constant-temperature gas (such as constant-temperature air) at 70-90℃ so that the constant-temperature copper alloy still has the target temperature when it enters the rotary forging equipment.

[0017] Furthermore, in S3, during the rotary forging process, the hammer's striking frequency is 600-1500 times / min, further to 800-1300 times / min, and then to 1000-1100 times / min; the hammer's radial compression is 0.2-2 mm / time, further to 0.4-1.8 mm / time, then to 0.6-1.5 mm / time, and then to 0.8-1.2 mm / time.

[0018] Furthermore, in S3, the radial deformation of the isothermal copper alloy is 10-20%, further to 12-18%, and even further to 14-16%, with a total deformation of 20-40%, further to 25-35%, and even further to 28-32%.

[0019] Optionally, in S3, the isothermal copper alloy with water on its surface is subjected to rotary forging.

[0020] Water on the surface of the constant-temperature copper alloy can act as a lubricant during the rotary forging process, which helps to improve the surface precision of the rotary forged copper alloy. This allows for the production of copper alloy products that can be delivered directly after secondary silicon diffusion, reducing the burden of post-processing and thus lowering costs.

[0021] Furthermore, in S4, the second siliconizing agent includes a silicon source, a silicon infiltration catalyst, and a filler, with a mass ratio of silicon source, silicon infiltration catalyst, and filler of 60-90:6-10:0-25; The silicon source is one or more of silicon powder and ferrosilicon powder; In the second gas mixture, the volume ratio of silane to hydrogen is 3:1.5-2.5.

[0022] Furthermore, in S4, the temperature is raised to 385-395℃ and held for 3.2-3.8 hours. Optionally, the heating rate is 1-3℃ / min.

[0023] Optionally, the treated copper alloy can be further used to manufacture copper alloy structural components such as copper alloy bearings, which can improve the wear resistance and service life of the relevant copper alloy structural components.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The processing method of the present invention can effectively improve the wear resistance of copper alloy and extend the service life of copper alloy.

[0025] (2) The processing method of the present invention helps to form a secondary silicon-doped layer with greater thickness, more stable structure and tighter bonding with copper alloy substrate on the surface of copper alloy, thereby significantly improving the wear resistance and service life of copper alloy.

[0026] (3) The processing methods of the present invention are all known and mature methods, which are easy to promote industrially. Detailed Implementation

[0027] The present invention will be described in detail below with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of the present invention can be combined with each other.

[0028] Unless otherwise specified, the relevant percentages refer to mass percentages.

[0029] Example 1 In this embodiment, the copper alloy processing method includes the following steps: S1. The copper alloy to be treated (round bar, 15 mm in diameter and 100 mm in length) is buried in a loading boat containing the first siliconizing agent (the copper alloy is covered by the first siliconizing agent). The loading boat is placed in a tube furnace, and nitrogen is introduced into the tube furnace. After the air is removed by the nitrogen, a first mixed gas containing silane and hydrogen is continuously introduced and kept flowing. The first mixed gas is ignited at the outlet. The temperature is increased by electricity at a rate of 2℃ / min to 530℃ (T1), held at 2.5h (t1), and cooled to room temperature with the furnace to obtain silicon-infiltrated copper alloy. The copper alloy (brass) has the following composition: Cu: 63wt%, Al: 4.0wt%, Mn: 2.5wt%, Si: 0.8wt%, with the balance being Zn and unavoidable impurities.

[0030] The first silicating agent consists of a silicon source, a silicating catalyst, an anti-sintering agent, and a filler. The mass ratio of the silicon source, silicating catalyst (ammonium chloride), anti-sintering agent (alumina powder), and filler (a mixture of silicon carbide powder and quartz powder in a 1:1 mass ratio) is 58:2:33:7. The silicon source is silicon powder. In the first mixed gas, the volume ratio of silane to hydrogen is 2:3.

[0031] S2. Place the silicon-impregnated copper alloy in a constant-temperature hot water (80°C) and maintain the temperature for 60 minutes to keep the temperature of the silicon-impregnated copper alloy constant at 80°C, thereby obtaining a constant-temperature copper alloy. S3. After the isothermal treatment, the isothermal copper alloy (with water on the surface, no drying is required after the isothermal treatment) is immediately subjected to rotary forging to obtain rotary forged copper alloy. During rotary forging, the hammer's striking frequency is 1050 times / min (f), and the radial compression of the hammer (i.e., the single feed amount of the hammer in the radial direction) is 1.2 mm / time (j). After rotary forging, the radial deformation of the isothermal copper alloy is 15% (b), and the total deformation is 30%.

[0032] S4. The forged copper alloy is buried in a loading boat containing a second siliconizing agent (the forged copper alloy is covered by the second siliconizing agent). The loading boat is placed in a tube furnace, and nitrogen is introduced into the tube furnace. After the air is removed by the nitrogen, a second mixed gas containing silane and hydrogen is continuously introduced and kept flowing. The second mixed gas is ignited at the outlet. The temperature is increased by electricity at a rate of 2℃ / min to 390℃ (T2). After holding at this temperature for 3.5h (t2), the temperature is cooled to room temperature with the furnace and removed from the furnace to obtain the copper alloy product. The second silicating agent consists of a silicon source, a silicating catalyst (ammonium chloride), and a filler (a mixture of silicon carbide powder and quartz powder in a 1:1 mass ratio), with a mass ratio of silicon source, silicating catalyst, and filler of 78:8:14; the silicon source is silicon powder; and the volume ratio of silane to hydrogen in the second mixed gas is 3:2.

[0033] Samples were taken from the obtained copper alloy products for annular paired friction and wear tests. The annular paired friction and wear tests were completed on an MM-200 testing machine under dry friction conditions.

[0034] Specifically, an annular sample was taken from the obtained copper alloy product, and a grinding test was conducted on the outer circumference of the block steel block (GCr15 bearing steel) and the annular sample.

[0035] Samples were taken from the obtained copper alloy product (copper alloy discs with a thickness of 15 mm were taken along the length of the copper alloy product) for hardness testing. The microhardness (Vickers hardness) of the outer circumference of the copper alloy product was measured at different distances from the radial direction to the center.

[0036] Example 2-15 Repeat Example 1, except for the differences shown in Table 1.

[0037] The relevant process parameters for Examples 1-15 are shown in Table 1.

[0038] Table 1 Summary of relevant process parameters for Examples 1-15

[0039] The hardness measurement results of the copper alloy products in Examples 1-15 are shown in Table 2.

[0040] Table 2 Summary of Hardness Measurement Results for Examples 1-15

[0041] The results of friction and wear tests on the copper alloy products of Examples 1-15 are shown in Table 3.

[0042] Table 3 Summary of friction and wear test results for copper alloy products in Examples 1-15

[0043] In summary, copper alloy products treated using the method of this invention have a thicker silicon-infiltrating layer, exhibit superior wear resistance, and help to effectively improve the service life of copper alloys.

[0044] The present invention provides an explanation for achieving the above-mentioned effects as follows: In this invention, after the copper alloy undergoes one silicon diffusion process, a relatively thin silicon diffusion layer is formed on the surface. Subsequently, the silicon-dipped copper alloy is placed in hot water for constant temperature treatment, which can further reduce the temperature of the silicon-dipped copper alloy and ensure that the temperature of each region within the silicon-dipped copper alloy is kept constant to the target temperature, laying the foundation for achieving high-quality rotary forging in the future. Subsequently, the isothermal copper alloy is subjected to rotary forging, laying the foundation for secondary silicon infiltration and the final formation of a thicker, more complete, harder, and more firmly bonded secondary silicon infiltrated layer with the copper alloy substrate. More specifically, during rotary forging, the silicon phase formed by the primary silicon infiltration is broken down, especially the coarse silicon phase, which is fully broken down, making the distribution of the silicon phase on the surface of the copper alloy more uniform and dispersed. This allows the silicon phase and the copper alloy substrate to form a mixed phase layer on the surface of the rotary-forged copper alloy. During the subsequent secondary silicon infiltration, silicon atoms can more easily enter the rotary-forged copper alloy through the copper alloy substrate in the mixed phase layer (the higher the concentration gradient, the faster the penetration process usually is), forming a new silicon phase. At the same time, silicon atoms will also penetrate into the rotary-forged copper alloy through the silicon phase in the mixed phase layer, causing the original silicon phase to grow further, ultimately forming a secondary silicon infiltrated layer with high continuity and greater thickness. The growth size of the original silicon phase into the interior of the copper alloy may also be larger, making the secondary silicon infiltrated layer more firmly "anchored" to the surface of the copper alloy, achieving a better strengthening effect. On the other hand, rotary forging is a diameter reduction deformation process. Under the action of deformation force, the radial dimension (such as diameter) of the copper alloy decreases, and the silicon-diffused phase is pressed radially into the interior of the copper alloy, like "nails" driven deeper into the copper alloy. This also makes the secondary silicon-diffused layer thicker and more stable, making the strengthening effect of the silicon-diffused phase more effective and its distribution more reasonable. In summary, this invention, through the combined action of primary silicon-diffusion, isothermal treatment, rotary forging, and secondary silicon-diffusion, helps to ultimately form a thicker secondary silicon-diffused layer with a certain gradient structure (the silicon-diffused phase decreases from the outside to the inside). This allows the secondary silicon-diffused layer to bond more firmly to the copper alloy substrate, withstand greater loads, and give the final copper alloy product a longer service life.

[0045] Comparative Example 1 Repeat Example 1, except that only S1 is performed, and S2-S4 are omitted.

[0046] Comparative Example 2 Repeat Example 1, except that only S2 is performed, and S1 and S4 are omitted.

[0047] Comparative Example 3 Repeat Example 1, except that only S4 is performed, and S1-S3 are omitted.

[0048] Comparative Example 4 Repeat Example 1, except that S4 is omitted.

[0049] Comparative Example 5 Repeat Example 1, except that S2 and S3 are omitted.

[0050] Comparative Example 6 Repeat Example 1, except that S1 is omitted.

[0051] Comparative Example 7 Repeat Example 1, except for the differences shown in Table 4.

[0052] Comparative Example 8 Repeat Example 1, except for the differences shown in Table 4.

[0053] Comparative Example 9 Repeat Example 1, except for the differences shown in Table 4.

[0054] Comparative Example 10 Repeat Example 1, except for the differences shown in Table 4.

[0055] Comparative Example 11 Repeat Example 1, except for the differences shown in Table 4.

[0056] Comparative Example 12 Repeat Example 1, except for the differences shown in Table 4.

[0057] Comparative Example 13 Repeat Example 1, except for the differences shown in Table 4.

[0058] Comparative Example 14 Repeat Example 1, except for the differences shown in Table 4.

[0059] Comparative Example 15 Repeat Example 1, except for the differences shown in Table 4.

[0060] Comparative Example 16 Repeat Example 1, except for the differences shown in Table 4.

[0061] Comparative Examples 17-20 Repeat Example 1, except for the differences shown in Table 4.

[0062] The relevant process parameters and hardness measurement results of Comparative Examples 1-20 are shown in Table 4.

[0063] Table 4 Summary of relevant process parameters for Comparative Examples 1-20

[0064] In Table 4, "-" indicates no operation was performed.

[0065] “①” indicates a failure rate of 15%.

[0066] “②” indicates a failure rate of 10%.

[0067] “③” indicates a failure rate of 12%.

[0068] “④” indicates an 11% failure rate.

[0069] If microcracks, cracks, or chips appear on the surface of the copper alloy product after processing, it is deemed unqualified.

[0070] The non-conforming rate is the percentage of non-conforming copper alloy products that occur when processing 100 pieces of copper alloy.

[0071] The hardness measurement results of the copper alloy products of Comparative Examples 1-20 are shown in Table 5.

[0072] Table 5. Summary of Hardness Measurement Results for Copper Alloy Products in Comparative Examples 1-20

[0073] The results of friction and wear tests on the copper alloy products of Comparative Examples 1-20 are shown in Table 6.

[0074] It can be seen that the average wear depth of the copper alloy products in each comparative example reached more than 0.21 mm, which is significantly higher than the average wear depth of the copper alloy products in Examples 1-15. The average frictional work of the copper alloy products in each comparative example reached over 93 kJ, which was significantly higher than the average frictional work of the copper alloy products in Examples 1-15. The average friction coefficient of the copper alloy products in each comparative example reached 0.185 or higher, which was significantly higher than the average friction coefficient of the copper alloy products in Examples 1-15. The average wear rate of the copper alloy products in each comparative example reached 10.5 mm·N. -1 ·m -1 All of the above are significantly higher than the average wear rate of the copper alloy products in Examples 1-15.

[0075] As can be seen from Comparative Examples 1-6, single silicon diffusion, constant temperature rotary forging, and double silicon diffusion all have a certain effect on the surface strengthening of copper alloys, but the strengthening effect is not ideal. Among them, secondary silicon diffusion has a weaker effect, while primary silicon diffusion and constant temperature rotary forging have better effects and the difference between the two is small. Even after combining two of the following methods—single-stage silicon diffusion, constant-temperature rotary forging, and secondary silicon diffusion—ideal results are still difficult to achieve.

[0076] In summary, this invention achieves better surface strengthening of copper alloys through the synergistic effects of primary silicon diffusion, constant temperature treatment, rotary forging, and secondary silicon diffusion. It obtains a thicker secondary silicon diffusion layer on the copper alloy surface, and makes the secondary silicon diffusion layer more firmly bonded to the copper alloy substrate, enabling it to withstand greater loads. This results in higher hardness, better wear resistance, and a longer service life for the final copper alloy product.

[0077] Table 6 Summary of friction and wear test results for copper alloy products in Comparative Examples 1-20

[0078] The above embodiments should be understood as being used only to illustrate the present invention more clearly, and not to limit the scope of the present invention. After reading the present invention, any modifications of the present invention in various equivalent forms by those skilled in the art fall within the scope defined by the appended claims.

Claims

1. A method for processing copper alloys, characterized in that, Includes the following steps: S1. The copper alloy to be treated is buried in the first siliconizing agent and placed in an atmosphere furnace in which a first mixed gas containing silane and hydrogen is continuously introduced. The temperature is raised to 450-610℃, held for 2-3 hours, and then cooled to obtain the siliconized copper alloy. S2. Place the silicon-impregnated copper alloy in a constant-temperature hot water bath to maintain the temperature of the silicon-impregnated copper alloy at 70-90℃ to obtain a constant-temperature copper alloy. S3. Perform rotary forging on the constant temperature copper alloy to obtain rotary forged copper alloy; S4. The forged copper alloy is embedded in the second siliconizing agent and placed in an atmosphere furnace with a second mixed gas containing silane and hydrogen continuously introduced. The temperature is raised to 380-400℃, held for 3-4 hours, and then cooled and removed from the furnace.

2. The method for processing copper alloys according to claim 1, characterized in that, In S1, the copper alloy contains 61-65 wt% Cu, 3.0-5.0 wt% Al, 1.5-3.5 wt% Mn, and 0.4-1.2 wt% Si, with the balance being zinc and unavoidable impurities.

3. The method for processing copper alloys according to claim 1, characterized in that, In S1, the first siliconizing agent includes a silicon source, a silicon infiltration catalyst, an anti-sintering agent, and a filler, with a mass ratio of 40-70:1-3:20-40:0-15; wherein, the silicon source is one or more of silicon powder and ferrosilicon powder; in the first mixed gas, the volume ratio of silane and hydrogen is 2:2.5-3.

5.

4. The method for processing copper alloys according to claim 1, characterized in that, In S1, the temperature is raised to 480-580℃ and held for 2.2-2.8 hours.

5. The method for processing copper alloys according to claim 1, characterized in that, In step S2, the silicon-impregnated copper alloy is placed in a constant-temperature hot water solution at 70-90°C and kept at that temperature for 50-70 minutes.

6. The method for processing copper alloys according to any one of claims 1-5, characterized in that, In S3, during rotary forging, the hammer's striking frequency is 600-1500 times / min, and the radial compression of the hammer is 0.2-2mm / time.

7. The method for processing copper alloys according to any one of claims 1-5, characterized in that, In S3, the radial deformation of the isothermal copper alloy is 10-20%, and the total deformation is 20-40%.

8. The method for processing copper alloys according to any one of claims 1-5, characterized in that, In S3, a constant-temperature copper alloy with water on its surface is subjected to rotary forging.

9. The method for processing copper alloys according to any one of claims 1-5, characterized in that, In S4, the second siliconizing agent includes a silicon source, a silicon infiltration catalyst, and a filler, with a mass ratio of 60-90:6-10:0-25; wherein the silicon source is one or more of silicon powder and ferrosilicon powder; in the second mixed gas, the volume ratio of silane and hydrogen is 3:1.5-2.

5.

10. The method for processing copper alloys according to any one of claims 1-5, characterized in that, In S4, the temperature is raised to 385-395℃ and held for 3.2-3.8 hours.

Citation Information

Patent Citations

  • Method for siliconizing surface of copper alloy

    CN115896684A